2001
DOI: 10.17656/jzs.10099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori among Dyspeptic Patients

Abstract: A total of 150 biopsies were collected from, dyspeptic patients  dyspeptic patients with and without ulcers from endoscopic unit of Azadi hospital, Dohuk. This study found a hiqh percentage (64%r) of Helicobacter pylori in the antrum of dyspeptic patients without endoscopic ulcers, while much lower, percentage was found in dyspeptic patients with gastric and duodenal ulcers which was (33%) and (20%) respectively. This low level of percentage was attributed to the inhibitory effect of antibiotics (Metronidazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…H. pylori becomes widely distributed throughout the world including Kurdistan region of Iraq in which studies had found that 65% of the dyspeptic patients were positive for H. pylori by culture [4] and 70.93% seropositive by ELISA IgG [5]. Antimicrobial drugs are extensively and empirically used for the treatment of H. pylori infections using different antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori becomes widely distributed throughout the world including Kurdistan region of Iraq in which studies had found that 65% of the dyspeptic patients were positive for H. pylori by culture [4] and 70.93% seropositive by ELISA IgG [5]. Antimicrobial drugs are extensively and empirically used for the treatment of H. pylori infections using different antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium can remain asymptomatic or can cause gastritis, gastric and duodenal ulcer and mucosa-associated lymphoid tissue lymphoma [3]. H. pylori is widespread in Kurdistan region of in which 65% of dyspeptic patients were positive for H. pylori by culture [4] and 70.93% by ELISA IgG [5]. Therefore, it has a significant health problem which requires eradication by using antimicrobial drugs [6,7].…”
Section: Introductionmentioning
confidence: 99%